The Effect of Marketing Improvisation on Customer Relationships of Commercial Banks in Jordan - Al-Nsour, Iyad A. (Jordan Journal of Business Administration, 2025)
This study aims to measure the effect of marketing improvisation on the relations of Jordanian commercial bank customers and determine the statistical differences in customer relations according to demographic variables (age, sex, education, and experience). The study population consists of all commercial bank customers in Jordan over 18 years. The age group between 15 and 46 years was about 63% of Jordan’s population of 11.2 millions in 2022. The convenience sampling was used and the responses reached 540. The research tool is a planned questionnaire and testing the hypotheses was carried out using structural equation modeling SEM. Based on the path-analysis results, the study found that marketing improvisation positively affected the relationships with commercial bank customers in Jordan and that there were no statistically significant differences between customers’ perceptions toward marketing improvisation according to demographics. Finally, the study presents a set of implications that enhance marketing improvisation in communication strategies in commercial banks in particular and businesses in general.